National Bank of Egypt : fiftieth anniversary commemoration lectures - Boreham, Gordon F. (Cairo, 1967)
The book provides a brief discussion of some of the important tasks and problems confronting bankers in developing countries and suggests some measures for refashioning banking systems in such countries, in order to make them more effective instruments in the process of development
Includes index
osc 14/8/17
Loans
Keywords: Banking; Egypt